2020
DOI: 10.2337/dc20-0723
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Patients With Hyperglycemia Affected by COVID-19: Can We Do More on Glycemic Control?

Abstract: An important prognostic factor in any form of infection seems to be glucose control in patients with type 2 diabetes. There is no information about the effects of tight glycemic control on coronavirus disease 2019 (COVID-19) outcomes in patients with hyperglycemia. Therefore, we examined the effects of optimal glycemic control in patients with hyperglycemia affected by COVID-19. RESEARCH DESIGN AND METHODS Fifty-nine patients with COVID-19 hospitalized with moderate disease were evaluated. On the basis of admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
430
2
17

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(468 citation statements)
references
References 25 publications
19
430
2
17
Order By: Relevance
“…Insulin remains a safe choice under all circumstances and is considered the first-line treatment in hyperglycemic critically-ill patients, and may require very high doses (see above). In patients infected with Covid-19, insulin infusion has been shown to be an effective method for achieving glycemic targets as well as reducing the risk of severe symptoms, when compared to patients that did not receive an infusion ( 70 ). It has been shown to modulate inflammatory mediators, suppress toll-like receptors (TLRs) implicated in innate immune responses, and suppress pro-inflammatory transcription factors in mononuclear cells ( 71 ).…”
Section: Type 2 Diabetes Management In Covid-19mentioning
confidence: 99%
“…Insulin remains a safe choice under all circumstances and is considered the first-line treatment in hyperglycemic critically-ill patients, and may require very high doses (see above). In patients infected with Covid-19, insulin infusion has been shown to be an effective method for achieving glycemic targets as well as reducing the risk of severe symptoms, when compared to patients that did not receive an infusion ( 70 ). It has been shown to modulate inflammatory mediators, suppress toll-like receptors (TLRs) implicated in innate immune responses, and suppress pro-inflammatory transcription factors in mononuclear cells ( 71 ).…”
Section: Type 2 Diabetes Management In Covid-19mentioning
confidence: 99%
“…This is also the case of COVID-19. It has been reported that a tight glycemic control with insulin infusion had a lower risk of severe disease than patients without insulin infusion [13].…”
Section: Glycemic Controlmentioning
confidence: 98%
“…People afflicted with diabetes constitute a large proportion of patients hospitalized for severe COVID-19, and appropriate inpatient management of hyperglycemia is important for improved outcomes. 19,20 Uncontrolled hyperglycemia has been linked to increased morbidity and worse outcomes in recent studies. 21 Severe COVID-19 infection may result in significant hyperglycemia not only in those with pre-existing diabetes but also in patients who have prediabetes, obesity or no previous risk factors.…”
Section: Management Of Hyperglycemia In Covid-19 Infected Patientsmentioning
confidence: 99%